(untitled) (Polifonia, 2013)
RESUMO: Neste artigo exploramos o discurso e o contradiscurso visívelem O outro pé da sereia, do autor moçambicano Mia Couto. Interrogamoscomo o estilo do autor auxilia a desconstrução da visãoeurocêntrica sobre a África e Moçambique utilizando, comoembasamento teórico de nossa análise, as obras de diversos escritorespós-coloniais. Argumentamos que o romance de Mia Couto sugere novaspossibilidades de leitura sobre a cultura e a história moçambicanas,divergindo de uma visão estereotipada presente em textos canônicos. PALAVRAS-CHAVE: pós-colonialismo, literatura africana,descolonização, hibridismo cultural ABSTRACT: In this article we explore the discourse and counterdiscoursevisible in Mia Couto’s O outro pé da sereia (The mermaid’sother foot). We investigate how the author’s style contributes to thedeconstruction of the Eurocentric view of Africa and Mozambique,employing as a theoretical basis for our analysis several postcolonialscholars’ works. We argue that the work of the Mozambican writersuggests new possibilities of reading about Mozambique’s history andculture. It is a revisiting and rewriting of a stereotyped vision of thecountry visible in some canonical texts. KEYWORDS: postcolonialism, African literature, decolonization, culturalhybridity